Agriculture in the Forest-Steppe Region of Khazaria - Koloda, Volodymyr Vasyl'ovyč, 1955- (East Central and Eastern Europe in the Middle Ages, 450-1450,, 2020)
In this book, Volodymyr Koloda and Serhiy Gorbanenko discuss the important role of agriculture in the socio-economic development of the Khazar Khaganate and its influence on neighboring peoples. Drawing on the methods of the natural sciences (such as palaeobotany, archeozoology, soil science, palaeoclimatology), the volume focuses on how agriculture became the basis of the economy of the Khazarian populace. Comparative analysis suggests a significant influence of the agricultural traditions of the Saltiv population on the neighboring tribes of the Eastern Slavs, such as Severians mentioned in the annals (the Romny culture of Left-Bank Ukraine) and Slavs on the Don (the Borshevo culture).